(untitled) (Research, Society and Development, 2022)
The gummy smile is defined as the excessive exposure of the maxillary gingiva during a smile. This condition has a varied etiology, and its correct identification is essential for planning an effective treatment. Depending on the identified diagnosis, and on the aesthetics to be achieved, there is a need for a multidisciplinary treatment, which may involve different specialties of dentistry. Therefore, the use of botulinum toxin (BT) represents one of the alternatives for the correction of gummy smile, being considered a simple, fast, non-invasive and effective method. Methods: This study aimed to evaluate the effectiveness of using botulinum toxin for the aesthetic improvement of the gummy smile, as well as its technique, advantages and disadvantages, through a literature review. Searches were carried out in the last 5 years in the databases Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature in Health Sciences (Lilacs), US National Library of Medicine National Institutes of Health (PubMed), Google Scholar, as well as as articles in databases of higher education institutions in Brazil. Results: With the purpose of improving the aesthetics of the gummy smile, allowing the patient to have a more harmonious smile, the use of botulinum toxin is a viable, safe, efficient and less invasive alternative when compared to reconstructive surgeries. Final considerations: The use of botulinum toxin is a great option for correcting the esthetic condition of the gummy smile, being easy to apply, with favorable cost/benefit and satisfactory to the patient.